WEBVTT
00:00:02.970 --> 00:00:13.880
Find the limit as π₯ approaches negative one of π₯ squared minus five π₯ minus six all divided by π₯ plus one plus π₯ to the seventh power plus one divided by π₯ cubed plus one.
00:00:14.240 --> 00:00:18.460
In this question, weβre asked to evaluate the limit of the sum of two rational functions.
00:00:18.490 --> 00:00:23.460
And we recall we can attempt to evaluate the limit of rational functions by using direct substitution.
00:00:23.710 --> 00:00:38.070
Substituting π₯ is equal to negative one into this function, we get negative one squared minus five times negative one minus six all divided by negative one plus one plus negative one to the seventh power plus one all divided by negative one cubed plus one.
00:00:38.360 --> 00:00:43.370
And then attempting to evaluate these expressions, we get zero over zero plus zero over zero.
00:00:43.400 --> 00:00:45.090
These are indeterminate forms.
00:00:45.420 --> 00:00:48.430
So we canβt just use direct substitution to evaluate this limit.
00:00:48.540 --> 00:00:53.160
And in fact we canβt even just use the fact that the limit of a sum is equal to the sum of the limits.
00:00:53.190 --> 00:00:58.240
Because if we try to apply direct substitution to each term, we also get an indeterminate form.
00:00:58.630 --> 00:01:02.040
Instead, letβs take a closer look at the two terms inside of our limit.
00:01:02.070 --> 00:01:03.350
Letβs start with the first term.
00:01:03.520 --> 00:01:05.330
The first term is a rational function.
00:01:05.330 --> 00:01:07.870
Itβs a quadratic divided by a linear function.
00:01:08.120 --> 00:01:13.020
And we know when we substitute π₯ is equal to negative one into our numerator, we get zero.
00:01:13.050 --> 00:01:17.930
So by using the remainder theorem, π₯ plus one must be a factor of our numerator.
00:01:18.260 --> 00:01:22.790
This would then allow us to evaluate the limit as π₯ approaches negative one of our first term.
00:01:23.000 --> 00:01:26.320
And in fact we could do something very similar for our second term.
00:01:26.490 --> 00:01:28.060
However, thereβs an easier method.
00:01:28.090 --> 00:01:31.980
We can just notice this is in the form of the limit of a difference of powers.
00:01:32.180 --> 00:01:35.960
This will then allow us to evaluate the limit of each term individually.
00:01:36.170 --> 00:01:40.830
So weβll start by writing the limits of a sum of two functions as the sum of their limits.
00:01:41.100 --> 00:01:45.460
And of course this result is only valid provided these two limits exist.
00:01:45.670 --> 00:01:48.570
Weβll start by evaluating the limit of the first function.
00:01:48.610 --> 00:01:50.680
Weβll do this by factoring our numerator.
00:01:51.010 --> 00:01:55.290
By the remainder theorem, we know that π₯ plus one must be a factor of this quadratic.
00:01:55.320 --> 00:01:56.510
We can find the other factor.
00:01:56.510 --> 00:01:58.360
Itβs equal to π₯ minus six.
00:01:58.570 --> 00:02:08.280
Using this expression, we can rewrite the limit of the first term as the limit as π₯ approaches negative one of π₯ plus one multiplied by π₯ minus six all divided by π₯ plus one.
00:02:08.530 --> 00:02:12.320
And now we see weβre taking the limit as π₯ approaches negative one of this function.
00:02:12.360 --> 00:02:17.130
Remember, we want to see what happens to the outputs of our function as π₯ approaches negative one.
00:02:17.410 --> 00:02:20.480
We donβt mind what happens when π₯ is equal to negative one.
00:02:20.580 --> 00:02:27.380
In particular, if π₯ is not equal to negative one, then π₯ plus one divided by π₯ plus one is just equal to one.
00:02:27.550 --> 00:02:34.960
So canceling the shared factor of π₯ plus one in the numerator and denominator will not change the limit of this function as π₯ approaches negative one.
00:02:35.310 --> 00:02:40.490
Therefore, the limit of this first term is just the limit as π₯ approaches negative one of π₯ minus six.
00:02:40.520 --> 00:02:44.980
And since this is a linear function, we can evaluate this limit by direct substitution.
00:02:45.280 --> 00:02:51.830
We substitute π₯ is equal to negative one into the linear function to get negative one minus six, which is equal to negative seven.
00:02:52.160 --> 00:02:53.570
However, weβre still not done yet.
00:02:53.570 --> 00:02:56.160
We still need to evaluate the limit of our second term.
00:02:56.370 --> 00:03:02.170
And to evaluate this limit, we need to recall the following result for the limit of a difference of powers.
00:03:02.410 --> 00:03:20.330
This tells us, for any real constants π, π, and π, where π is nonzero, the limit as π₯ approaches π of π₯ to the πth power minus π to the πth power all divided by π₯ to the πth power minus π to the πth power is equal to π over π multiplied by π to the power of π minus π.
00:03:20.780 --> 00:03:27.510
And this is provided π to the πth power, π to the πth power, and π to the power of π minus π all exist.
00:03:27.810 --> 00:03:31.340
Before we apply this result, we need to rewrite our function in this form.
00:03:31.510 --> 00:03:37.220
First, we rewrite our numerator as π₯ to the seventh power minus negative one all raised to the seventh power.
00:03:37.550 --> 00:03:42.110
And similarly, we rewrite our denominator as π₯ cubed minus negative one all cubed.
00:03:42.450 --> 00:03:53.200
This means weβve now rewritten the limit of our second term as the limit as π₯ approaches negative one of π₯ to the seventh power minus negative one to the seventh power all divided by π₯ cubed minus negative one all cubed.
00:03:53.520 --> 00:03:56.350
And we can see this is in the form of our limit result.
00:03:56.470 --> 00:04:00.980
π is equal to negative one, π is equal to seven, and π is equal to three.
00:04:01.310 --> 00:04:06.490
And now we can evaluate the limit of this second term by substituting these values into our formula.
00:04:06.550 --> 00:04:10.910
Its limit is seven over three times negative one to the power of seven minus three.
00:04:11.250 --> 00:04:13.040
We can then evaluate this expression.
00:04:13.070 --> 00:04:14.900
Seven minus three is equal to four.
00:04:14.930 --> 00:04:18.650
So we just have seven over three multiplied by negative one to the fourth power.
00:04:19.000 --> 00:04:21.860
And negative one raised to the fourth power is just equal to one.
00:04:22.150 --> 00:04:30.320
Therefore, weβve shown the limit of the first term in our function is equal to negative seven, and the limit of the second term in our function is equal to seven over three.
00:04:30.420 --> 00:04:32.810
So the limits of both of these functions exist.
00:04:32.850 --> 00:04:37.010
Therefore, the limit of the sum of these functions is equal to the sum of the limits.
00:04:37.190 --> 00:04:42.370
And if we add these two values together, we get negative 14 over three, which is our final answer.
00:04:42.740 --> 00:04:57.150
Therefore, we were able to show the limit as π₯ approaches negative one of π₯ squared minus five π₯ minus six all divided by π₯ plus one plus π₯ to the seventh power plus one over π₯ cubed plus one is equal to negative 14 over three.